Control of crystallization in two‐phase blends of poly(phenylene sulfide) and poly(vinylpyrrolidone). Issue 2 (20th November 2020) - Nara, Saori; Watanabe, Kazuhiro; Oyama, Hideko T.; Saito, Hiromu
Abstract: This paper reports for the first time the use of poly( N ‐vinylpyrrolidone) (PVP) as an effective additive for controlling the melt crystallization behavior of poly( p ‐phenylene sulfide) (PPS). The PPS/PVP blends form two‐phases, whose melt crystallization temperature decreases drastically upon the addition of PVP accompanied by a delayed onset of crystallization and a decreased crystallization rate. Monitoring spherulite growth during isothermal annealing revealed that in blends with less than 5 wt% of PVP the diminution of the crystallization rate of PPS is due to a decrease in both the nucleation rate and the spherulite growth rate, whereas in blends with higher PVP content the falloff in rate is mainly caused by slow nucleation. A change was observed in the glass transition temperature and melting temperature of PPS upon blending, suggesting that the blends are partially miscible. The delay in crystallization is likely due to the partial miscibility disturbing exclusion of PVP from the crystalline growth front. Abstract : In PPS/PVP blends, the addition of amorphous PVP disturbs the ordered structure of PPS spherulites and significantly decreases the melt crystallization temperature (Tmc ) of PPS even with a small amount of PVP (<10 wt%). It is demonstrated that the Tmc, which is important in molding processes, is controllable by changing the PVP content added to PPS barely sacrificing the high melting temperature of PPS.